Christianity in India : conversion, community development, and religious freedom - Shah, Rebecca; Carpenter, Joel A. (Fortress Press, 2018)
Christianity has been present in India since at least the third century, but the faith remains a small minority. Even so, Christianity is growing rapidly in parts of the subcontinent, and has made an impact far beyond its numbers. Yet Indian Christianity remains highly controversial, and it has suffered growing discrimination and violence. This book shows how Christian converts and communities continue to make contributions to Indian society, even amid social pressure and violent persecution. In a time of controversy in India about the legitimacy of conversion and the value of religious diversity, Christianity in India addresses the complex issues of faith, identity, caste, and culture. It documents the outsized role of Christians in promoting human rights, providing education and healthcare, fighting injustice and exploitation, and stimulating economic uplift for the poor. Readers will come away surprised and sobered to learn how these active initiatives often invite persecution today. The essays draw on intimate and personal encounters with Christians in India, past and present, and address the challenges of religious freedom in contemporary India.